2020
DOI: 10.3390/ijerph17249410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentric Single-Leg Decline Squat Exercise on the Morphological and Structural Properties of the Vastus Lateralis and Patellar Tendon

Abstract: The purpose was to examine the effect of 6-week eccentric single-leg decline squat (SLDSe) training with two technical execution times (3 s or 6 s) on changes related to the structural properties of the vastus lateralis (VL) and patellar tendon (PT). Thirty-six physical active volunteers were randomly divided into three groups: control group (CG, n = 13, age = 20.8 ± 1.9 years, no intervention program), experimental group 1 (EG1, n = 11, age = 21.6 ± 2.5 years, execution time = 6 s) and experimental group 2 (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…The results obtained in tendon thickness agree with previous investigations that have analyzed the thicknesses of healthy and pathological tendons [ 16 , 40 ]. On the other hand, although most of the investigations that have achieved hypertrophic increases in the PT have used at least twelve weeks of intervention by means of eccentric exercise [ 10 , 11 , 33 , 35 ], the present study, according with Abian et al [ 16 ], shows that six weeks of intervention using the SLDSe exercise focused on its eccentric phase are sufficient to increase the thickness of the PT, independently of the execution time of the eccentric contraction performed. This may be due to the high load (80% of the eccentric 1 RM) and the type of exercise (SLDSe) used in our intervention program.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results obtained in tendon thickness agree with previous investigations that have analyzed the thicknesses of healthy and pathological tendons [ 16 , 40 ]. On the other hand, although most of the investigations that have achieved hypertrophic increases in the PT have used at least twelve weeks of intervention by means of eccentric exercise [ 10 , 11 , 33 , 35 ], the present study, according with Abian et al [ 16 ], shows that six weeks of intervention using the SLDSe exercise focused on its eccentric phase are sufficient to increase the thickness of the PT, independently of the execution time of the eccentric contraction performed. This may be due to the high load (80% of the eccentric 1 RM) and the type of exercise (SLDSe) used in our intervention program.…”
Section: Discussionsupporting
confidence: 90%
“…The thickness of the PT was measured by B-mode ultrasonography (LOGIQ E9, GE Healthcare, Milwaukee, WI, USA) with a 5.5 cm, high frequency 6–15 MHz linear probe. The participants lay supine on a stretcher, with the knee flexed to 15° [ 16 , 22 ]. The transducer was placed parallel to the direction of the PT fibers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ultrasonography has become a standard method for measuring the mechanical properties of the tendon in vivo [ 8 ], like stiffness which can be assessed reliably and with validity using sonoelastography [ 9 , 10 ]. The majority of studies which use sonoelastography to evaluate tendon stiffness are focused on assessing the Achilles tendon [ 10 , 11 ], although some recent studies on the patellar tendon (PT) can also be found [ 12 , 13 , 14 , 15 ]. Porta et al [ 13 ] assessed the reliability and reproducibility of sonoelastography for describing the stiffness of the patellar tendon and found that a healthy patellar tendon presents high elasticity with excellent values of intra-examiner and inter-examiner reproducibility.…”
Section: Introductionmentioning
confidence: 99%